Optimization of Power Loss Reduction in IGBT-based Three-Phase Rectifiers using Discontinuous Pulse Width Modulation Method: A Simulation-Based Analysis with QSpice and Fuji IGBT Simulator - Pratama, Rio; Alam, Syaiful; Soedjarwanto, Noer; Komalasari, Endah (Universitas Syiah Kuala, 2025)
The increasing demand for electricity supply is evident across various modern industrial sectors. Electrification advancements in the transportation industry aim to address environmental and energy issues and continue to evolve. Charging electric vehicles is one of the most important aspects of electrification in the transportation sector. This study develops and simulates a three-phase IGBT-based rectifier using the Discontinuous Pulse Width Modulation 60-degree (DPWM1) method to optimize power loss reduction in a 200-kW charging system. The DPWM method has been shown to reduce power losses by up to 44% compared to the conventional Sinusoidal Pulse Width Modulation (SPWM) method under full load conditions, resulting in reduced heat and cooling requirements for the devices. Simulations show that with the appropriate use of filters, the total harmonic distortion of current (THDi) of the AC input side is reduced to 2.267%, minimizing the negative impacts on the grid. In addition, implementing feedforward control maintains DC voltage stability despite load variations, improving system efficiency and reliability.